Refléter le passé : les faux bronzes en porcelaine sous le règne de l’empereur Qianlong (1735-1785) - Stéphanie Brouillet (Les Cahiers de Framespa)
Porcelains adopting the form of ancient bronzes and their cover imitating bronze and its oxidations are characteristic of the Qianlong period (1735-1795). They are proof of the importance of ancient bronzes – a cultural, social, political, and artistic reference under Qianlong’s reign. The Emperor was eager to prove its reign to be part of the Chinese dynasties by shedding light on older productions and paying them tribute through contemporary creations. These fake bronzes in porcelain also reflect the way Qianlong controlled every aspect of the artistic production, and his love of “trompe-l’oeil” in the decorative arts.